2019
DOI: 10.22219/jpbi.v5i2.7952
|View full text |Cite
|
Sign up to set email alerts
|

The integration of PBL and cooperative script to empower critical thinking skills of biology students

Abstract: One of the factors lead to the low critical thingking skill is the implementation of teacher center learning. The purpose of this research was to determine the effect of the implementation of Problem-based Learning integrated with Cooperative Script to students’ critical thinking skills. This quasi-experimental research was done in senior high schools of Samarinda, Indonesia. The design used in this research was nonequivalent pretest - posttest control group design. The sample was the class XI  students of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Boleng and Maasawet adopted the PBL teaching method to teach students cooperative scripts. ey found that the PBL teaching method has a significant impact on improving students' critical thinking and can be applied to teaching literature [7]. Zhou found that the PBL teaching method can improve students' analytical, openness, and fairness qualities and their explanatory abilities in learning English [8].…”
Section: Introductionmentioning
confidence: 99%
“…Boleng and Maasawet adopted the PBL teaching method to teach students cooperative scripts. ey found that the PBL teaching method has a significant impact on improving students' critical thinking and can be applied to teaching literature [7]. Zhou found that the PBL teaching method can improve students' analytical, openness, and fairness qualities and their explanatory abilities in learning English [8].…”
Section: Introductionmentioning
confidence: 99%
“…Most learning in schools still have not implemented a proven learning model that can empower critical thinking skills. Problem-based learning is a learning model that is often reported to be able to improve students' critical thinking skills (Birgili, 2015;Boleng & Maasawet, 2019;Masek & Yamin, 2012;Sada et al, 2016;Sulaiman & Elnetthra, 2014). Project-based learning is another cooperative learning that is also reported to have a positive impact on the development of students' thinking skills (Eldiva & Azizah, 2019;Issa & Khataibeh, 2021;Sasson et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In the development of cooperative script learning, it has undergone many adaptations, giving birth to several notions and forms that are slightly different from one another, but in essence the same. According to Boleng & Maasawet (2019) the cooperative script learning model, also called cooperative script, is a lesson in which students work in pairs and orally summarize parts of the material they learn in the classroom. Meanwhile, according to (Harefa et al (2019 andR et al (2020) cooperative script learning is learning that organizes student interactions such as illustrations of students' social life with their environment as individuals, in families, community groups, and wider society.…”
Section: Introductionmentioning
confidence: 99%